Disruption of FGF Signaling Ameliorates Inflammatory Response in Hepatic Stellate Cells - Wang, Cong; Li, Yuelong; Li, Hao; Zhang, Yali; Ying, Zhangguo; Wang, Xuye; Zhang, Tingting; Zhang, Wenshu; Fan, Zhichao; Li, Xiaokun; Ma, Jisheng; Pan, Xuebo (Frontiers in Cell and Developmental Biology, 2020)
Fibroblast growth factors (FGFs) binding with fibroblast growth factor receptors (FGFRs) is a well-documented event that regulates liver development and homeostasis in autocrine, paracrine, and endocrine manners. Recent research reveals that hepatic stellate cell (HSC) plays a fundamental role of in liver immunology. However, how FGF signaling in HSCs to regulating liver inflammation remains unclear. Here we report that FGF promoted NF-κB signaling in human HSCs, which was associated with FGFR1 expression. Both FGF and NF-κB signaling in HSCs were compromised by a tyrosine kinase inhibitor of FGFR1. After stimulating HSCs with pro-inflammatory cytokine, the expression of multiple FGF ligands was significantly increased. Moreover, disruption of FGF signaling with FGFR inhibitors reduced the DNA trap, an inflammatory response, NF-κB nuclear translocation induced by TNFα, and reduced expression of matrix metalloproteinase-9 (MMP-9). Interestingly, FGF21 significantly alleviated the inflammation responses in the concanavalin A (Con A) induced acute injured liver. It is well documented that, unlike canonic FGFs that elicit signals through FGFR-heparan sulfate complex, FGF21 elicits different signaling through activating the FGFR-KLB complex. Therefore, the finding here indicates the urgency to develop pathway-specific inhibitors that only suppress canonical FGF, but not FGF21, signaling for suppressing inflammation in the liver, which is presented in all stages of diseased liver.